Intermittent hypobaric hypoxia exposure increases ventilatory treshold but not running performance in triathletes - Rodriguez, F. A.; Iglesias, X.; Barrero, A.; Abalos, X.; Moreno, D.; Abellan, R.; Segura, J. (Sport Science Research Group, INEFC-Barcelona, 2011)
Short-term intermittent hypoxia exposure (IHE) combined with sea level training has shown to improve cycling performance in world-class track cyclists (1), and middle-distance swimming performance (2-3) or VO2max and ventilatory threshold in competitive swimmers (2-3). This study investigated the effect of IHE on aerobic capacity and running performance in triathletes.